Analisis Faktor yang Berhubungan dengan Pemberian ASI Eksklusif - Fitriana Ibrahim; Bhakti Rahayu (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; giving exclusive breastfeeding to newborns is one of the efforts to prevent infectious diseases, malnutrition, and mortality in infants and toddlers. Objectives; know the relationship between knowledge, education, and work of mothers with exclusive breastfeeding. Method; This type of research is descriptive-analytical. With a cross-sectional approach with a sample size of 48 breastfeeding mothers and the sampling technique with total sampling. Data analysis was performed using the chi-square test. Result; that shows there is a relationship between knowledge and education with exclusive breastfeeding. There is no relationship between work and exclusive breastfeeding. Conclusion; that knowledge and education of breastfeeding mothers have a significant relationship with exclusive breastfeeding.